Route of administration for illicit prescription opioids: a comparison of rural and urban drug users - Havens Jennifer R; Young April M; Leukefeld Carl G (BMC, 2010)
Abstract Background Nonmedical prescription opioid use has emerged as a major public health concern in recent years, particularly in rural Appalachia. Little is known about the routes of administration (ROA) involved in nonmedical prescription opioid use among rural and urban drug users. The purpose of this study was to describe rural-urban differences in ROA for nonmedical prescription opioid use. Methods A purposive sample of 212 prescription drug users was recruited from a rural Appalachian county (n = 101) and a major metropolitan area (n = 111) in Kentucky. Consenting participants were given an interviewer-administered questionnaire examining sociodemographics, psychiatric disorders, and self-reported nonmedical use and ROA (swallowing, snorting, injecting) for the following prescription drugs: buprenorphine, fentanyl, hydrocodone, hydromorphone, methadone, morphine, OxyContin® and other oxycodone. Results Among urban participants, swallowing was the most common ROA, contrasting sharply with substance-specific variation in ROA among rural participants. Among rural participants, snorting was the most frequent ROA for hydrocodone, methadone, OxyContin®, and oxycodone, while injection was most common for hydromorphone and morphine. In age-, gender-, and race-adjusted analyses, rural participants had significantly higher odds of snorting hydrocodone, OxyContin®, and oxycodone than urban participants. Urban participants had significantly higher odds of swallowing hydrocodone and oxycodone than did rural participants. Notably, among rural participants, 67% of hydromorphone users and 63% of morphine users had injected the drugs. Conclusions Alternative ROA are common among rural drug users. This finding has implications for rural substance abuse treatment and harm reduction, in which interventions should incorporate methods to prevent and reduce route-specific health complications of drug use.